Wyrób tekstylny z cmentarzysku kultury łużyckiej w Dąbrowie, pow. wieluński. - Radosław Janiak; Joanna Słomska-Bolonek (Acta Universitatis Lodziensis: Folia Archaeologica)
Excavations in 2023 conducted at the cemetery of the Lusatian culture population in Dabrowa, state. 2, Wieluń district contributed to the discovery of an ashless corpse burial no. 24. Dated to the Halstatt period, the grave contained burnt human bones, fragments of pottery from various vessels, and metal objects showing features of burning in the fire. Among the metal wares, there was a fragment of an iron plate, on the surface of which mineralized remains of fabric were preserved. Technological analysis showed that we are dealing with a fabric of very high quality, which used thin yarn and high-density half-baket weave. None of the fabrics discovered so far in the Vistula and Oder river basins had such similar characteristics. On the other hand such textiles were exhibited by finds from the Hallstatt culture circle or the Scandinavian area. This product may be an import, although its production in a local weaving workshop cannot be unequivocally ruled out.